The Role of Human Capital in Structural Change and Growth in an Open Economy: Innovative and Absorptive Capacity Effects - Brita Bye; Taran Faehn (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Since the financial crisis in 2008, slow growth has riddled Europe and the Covid-19 pandemic is amplifying the challenge. Promoting economic growth and transforming to a more knowledge-based industrial structure will be high on the agenda for the coming decades. We study how more and better human capital can contribute to knowledge accumulation and structural change by means of a dynamic endogenous growth model, with Norway as a numerical case. Human capital has two main roles in productivity growth: to increase the innovative capacity by participating in research and development (R&D), and to increase the absorptive capacity in sectors that trade and can learn from abroad. We find that in a small, open economy sectors where human capital, R&D and trade interact, and enable absorption, tend to grow fastest.
Keywords: C68; F43; O30; O41; 330; absorptive capacity; computable general equilibrium model; endogenous growth; human capital; innovation; research and development